The Effect of Purple Sweet Potato Extract on The Circulating Endothelial Cell (CEC) levels in Rat Model of Diabetes - Emilia Puspita Sari; Edi Junaidi; Heni Fatmawati (Faculty of Medicine, University of Jember, 2017)
Diabetes mellitus is a metabolic disease with impaired metabolism of carbohydrates, fats and proteins are characterized by hiperglycemia caused by insufficiency of insulin secretion and insulin resistance. Diabetes mellitus is the leading cause of death in Indonesia, especially in developing countries. Most (90%) classified as type 2 diabetes mellitus and 10% of type 1 diabetes mellitus. In DM, increased oxidative stres. DM oxidative stres due to the increase of free radicals in the body. Oxidative stres can lead to irreversible endothelial injury that would lead to the loss of endothelial cells characterized by the expression of CD 146. Ipomoea batatas L. anthocyanin-containing compound is an antioxidant that can reduce free radicals and reduce oxidative cell damage caused by free radicals. From the analysis of the data obtained Ipomoea batatas L. mempuyai influence on the content of the CEC of 42.5%.